STUDI BULAN ASADHA TENTANG KEPEDULIAN AJARAN AGAMA BUDDHA TERHADAP KEBAHAGIAAN SEMUA MAKHLUK HIDUP - Arif Muzayin Shofwan (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2026)
In the month of Asadha, the Buddha first gave a lecture to his followers which contained concern for the happiness of all living beings, both visible and invisible. This qualitative research using a literature study will examine the concept of concern from Buddhist teachings for the happiness of all living creatures. The data analysis technique uses content analysis by sorting things according to the focus and objectives of the research. This research produced the following findings. First, the commemoration of the holy month of Asadha teaches Buddhists the importance of understanding the nature of human life and its purpose. With his concern, the Buddha explained the Four Noble Truths, namely: (1) the truth of suffering; (2) the truth of the origin of suffering; (3) the truth of the cessation of suffering; and (4) the truth of the path leading to the cessation of suffering. Second, the commemoration of the holy month of Asadha teaches Buddhists the importance of the path to the cessation of suffering which is usually called the "Noble Eightfold Path" or "Middle Path", namely a path that Buddhists must take to lead to the cessation of suffering and obtain unlimited happiness and enlightenment.